Management Control Systems and Startup Legitimacy on Funding Success - Heni Indah Pratiwi; Galih Fajar Muttaqin (Jurnal Akuntansi Indonesia, 2026)
This study aims to explore the dual role of Management Control Systems (MCS) as a mechanism for building startup legitimacy and its impact on funding success. Grounded in institutional theory and signaling theory, this research develops a conceptual framework that views MCS not only as an internal control tool but also as a strategic instrument for gaining legitimacy in the eyes of investors. The study employs an explanatory sequential mixed-methods design. Data were collected through a survey of 100 startups in Indonesia in 2025, as well as in-depth interviews with 15 founders and 10 investors. Quantitative analysis using Structural Equation Modeling (SEM) with SmartPLS 4.0 reveals that MCS formalization and its use as a signal have a positive and significant effect on legitimacy, which in turn increases the probability of funding success. Furthermore, legitimacy is found to be a significant mediating variable in this relationship. Internally, the implementation of MCS also yields substantive benefits, including improved financial discipline and strategic clarity. These findings provide theoretical contributions to the MCS literature within the entrepreneurial context and offer practical guidance for startup founders in leveraging MCS as a tool to build credibility and attract investment.Keywords: Management Control System (MCS), legitimacy, startup funding, institutional theory, signaling theory.